Bacteriophages and their potential for treatment of metabolic diseases - Youpeng Deng; Shouwei Jiang; Hanyu Duan; Haonan Shao; Yi Duan (Journal of Diabetes, 2024)
Abstract Recent advances highlight the role of gut virome, particularly phageome, in metabolic disorders such as obesity, type 2 diabetes mellitus, metabolic dysfunction‐associated fatty liver disease, and cardiovascular diseases, including hypertension, stroke, coronary heart disease, and hyperlipidemia. While alterations in gut bacteria are well‐documented, emerging evidence suggests that changes in gut viruses also contribute to these disorders. Bacteriophages, the most abundant gut viruses, influence bacterial populations through their lytic and lysogenic cycles, potentially modulating the gut ecosystem and metabolic pathways. Phage therapy, previously overshadowed by antibiotics, is experiencing renewed interest due to rising antibiotic resistance. It offers a novel approach to precisely edit the gut microbiota, with promising applications in metabolic diseases. In this review, we summarize recent discoveries about gut virome in metabolic disease patients, review preclinical and clinical studies of phage therapy on metabolic diseases as well as the breakthroughs and currently faced problems and concerns.